EVALUASI KOLABORASI KELEMBAGAAN DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI (DAS) AIR BENGKULU (STUDI KASUS DIDESA RINDU HATI, KEC. TABA PENANJUNG, KAB. BENGKULU TENGAH) - Henny Aprianty; Heru Purnawan; Kauri, Ocha Putri (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
A river basin (DAS) is a space where natural resources, especially vegetation, land and water, are located and stored as well as a place where humans live to utilize these natural resources to meet their daily needs. Bengkulu Provincial Regional Regulation UUD Number 1 of 2017 concerning Management of Bengkulu River Watersheds (DAS), states that river watersheds are a part of water resources which have an important meaning for human survival and welfare. This research uses a qualitative descriptive method approach and this research uses a case study method, Collaborative program evaluation related to Evaluation of Institutional Collaboration in the Management of the Air Bengkulu Watershed (DAS) based on Regional Regulation Number 1 of 2017 concerning Management of the Watershed (DAS), namely: Communication, Coordination of Decision Making, Conflict Resolution, Monitoring and Evaluation, Procedures and Improvements. The goal is to find out what steps have been fulfilled. Collaborative models and processes in evaluating institutional collaboration in the management of the Air Bengkulu watershed have the leadership of institutions/agencies that make monitoring and evaluation of institutional collaboration in the management of the Air Bengkulu watershed implemented. This integration does not make the units of the institution/agency unite because in its implementation it is basically a mixture where the relevant institutions/agencies have their respective duties and functions. Implemented in accordance with spatial plans and water resource management patterns in accordance with the provisions of applicable laws and regulations, carried out in a coordinated manner involving relevant agencies at cross-administrative boundaries as well as the role of the community, prioritizing the integration of the interests of various sectors and regions, becoming the basis for the formulation strategy to maintain the Carrying Capacity of the DAS which includes the formulation of policies, programs and activities.